Fuzzy pH control of sugarcane juice for sugar production (Research, Society and Development, 2020)
A proposal to control the pH of the broth in sugar mills is presented in this work. Because it is a system with nonlinear characteristics and disturbances, the conventional control methods do not satisfy the usual requirements of the process. Among these conventional methods, we highlight the PID controller, which is basically linear. Extending the possibilities of action, the control proposal presented in this work proved to be quite satisfactory, by using fuzzy logic in a predictive way in the consideration of the effect of the disturbances in an intelligent way. The details of the proposed controller are presented, including some simulation results. The effectiveness of the proposed controller is illustrated by simulation, showing graphically the disturbances and the consequent control action, which eliminates the steady state error. The comparison of the results obtained with conventional PID controllers and the fuzzy controllers shows the predictive action of the fuzzy controllers allowing a significant reduction in the variability of the steady state error. In addition, this architecture can be modified to include other disturbances for other applications. Thus, the present proposal can be used in general to control non-linear and multivariable systems.